Identity Matters: Indonesia's approach towards territorial disputes in South-east Asia. (2nd July 2020) - Prasetya, Dion Maulana; Haffsari, Peggy Puspa; Estriani, Heavy Nala
ABSTRACT: After gaining independence in 1945, Indonesia's foreign policy demonstrated an active role in resolving maritime disputes in South-east Asia. The settlement effort is inseparable from the role of Association of Southeast Asian Nations (ASEAN) as the cornerstone of Indonesia's foreign policy. In responding to the maritime boundary disputes in the South-east Asian region, for instance, Indonesia relates to the ASEAN "spirit of dialogue", which emphasises the principles of diplomacy, negotiations and cooperation in conducting peaceful settlements. However, under Joko Widodo's administration, Indonesia did not always prioritise its institutional aspects in responding to maritime conflicts in South-east Asia. In some cases, Indonesia acts unilaterally, especially when the case concerns its maritime identity. This article will try to examine Indonesia's approach towards territorial disputes under Jokowi's administration, by asking two questions: (1) Is Indonesia's approach towards territorial disputes more institutionalist or realist? (2) If both apply, to what extent has Indonesia become institutionalist or realist? By using a constructivist approach, this article argues that Indonesia embraces two identities that function hierarchically. Indonesia identifies itself first as a maritime nation, and second as a regional leader. When it comes to settling sea territorial disputes, Indonesia's geopolitical behaviour has always been shadowed by the maritime nation identity.